The kidney cytochrome P-450 2C23 arachidonic acid epoxygenase is upregulated during dietary salt loading - Holla, Vijaykumar R. (American Society for Clinical Investigation, 1999)
Excess dietary salt intake induces the activity of the kidney arachidonate epoxygenase and markedly increases the urinary excretion of its metabolites. The epoxyeicosatrienoic acids, products of the kidney P-450 arachidonate epoxygenase, inhibit distal nephron Na(+) reabsorption. Nucleic acid hybridization studies demonstrated the expression of P-450s 2C23, 2C24, and 2C11 as the predominant kidney 2C isoforms and the lack of significant dietary salt-dependent transcriptional regulation of these proteins. Recombinant P-450s 2C11, 2C23, and 2C24 catalyze arachidonate metabolism to mixtures of epoxy- and monohydroxylated acids. Whereas the arachidonate 11,12-olefin was the preferred target for epoxidation by P-450 2C23 (57% of total products), P-450s 2C11 and 2C24 epoxidized the 11,12-olefins and 14,15-olefins with nearly equal efficiency. Stereochemical comparisons demonstrated that the regiochemical and enantiofacial selectivity of P-450 2C23 matched that of the kidney microsomal epoxygenase and that excess dietary salt does not alter the regiochemical or stereochemical selectivity of the kidney arachidonate epoxygenase. Inhibition and immunoelectrophoresis experiments using antibodies raised against recombinant P-450s 2C11 and 2C23 demonstrated that P-450 2C23 is the major 2C arachidonic acid epoxygenase in the rat kidney and the renal P-450 isoform regulated by excess dietary salt intake.